Comparative cytogenetics of six Indo‐Pacific moray eels (Anguilliformes: Muraenidae) by chromosomal banding and fluorescence in situ hybridization. Issue 3 (4th August 2015) - Coluccia, E.; Deidda, F.; Cannas, R.; Lobina, C.; Cuccu, D.; Deiana, A. M.; Salvadori, S.
<x xml:space="preserve">Abstract</x> A comparative cytogenetic analysis, using both conventional staining techniques and fluorescence in situ hybridization, of six Indo‐Pacific moray eels from three different genera (Gymnothorax fimbriatus, Gymnothorax flavimarginatus, Gymnothorax javanicus, Gymnothorax undulatus, Echidna nebulosa and Gymnomuraena zebra), was carried out to investigate the chromosomal differentiation in the family Muraenidae. Four species displayed a diploid chromosome number 2n = 42, which is common among the Muraenidae. Two other species, G. javanicus and G. flavimarginatus, were characterized by different chromosome numbers (2n = 40 and 2n = 36). For most species, a large amount of constitutive heterochromatin was detected in the chromosomes, with species‐specific C‐banding patterns that enabled pairing of the homologous chromosomes. In all species, the major ribosomal genes were localized in the guanine‐cytosine‐rich region of one chromosome pair, but in different chromosomal locations. The (TTAGGG)n telomeric sequences were mapped onto chromosomal ends in all muraenid species studied. The comparison of the results derived from this study with those available in the literature confirms a substantial conservation of the diploid chromosome number in the Muraenidae and supports the hypothesis that rearrangements have occurred that have diversified their karyotypes. Furthermore, the finding of two species with different diploid chromosome numbers suggests that additional chromosomal rearrangements, such as Robertsonian fusions, have occurred in the karyotype evolution of the Muraenidae.